1984
DOI: 10.1523/jneurosci.04-08-02106.1984
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of the vestibular hair cell-afferent fiber synapse in the frog

Abstract: The isolated, intact, membranous labyrinth of the frog (Rana temporaria) has been investigated electrophysiologically in vitro to determine the nature of the transmitter substance at the synapse between the vestibular hair cells and afferent fibers. Spontaneous synaptic activity can be monitored with intra-axonal recordings from the afferents. Increased K+ in the bath results in an increase in frequency of presynaptic release, as indicated by an increased frequency of spontaneous synaptic potentials. Adding Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
35
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(48 citation statements)
references
References 26 publications
12
35
1
Order By: Relevance
“…The functional site could be either postsynaptic to the hair cell or postsynaptic to the lateral efferent input to spiral ganglion cell dendrites beneath IHCs. The presence of ␦1 postsynaptic to hair cells is consistent with the hypothesis that an excitatory amino acid is the neurotransmitter of hair cells (Annoni et al, 1984;Soto and Vega, 1988;Bledsoe et al, 1989; for review, see Eybalin, 1993;Puel, 1995). Spiral and vestibular ganglion neurons express many glutamate receptors including AMPA, kainate, and NMDA ionotropic receptors and several metabotropic receptors (Ryan et al, 1991;Eybalin, 1992b, 1995;Demêmes et al, 1995;Niedzielski and Wenthold, 1995;Usami and Ottersen, 1995).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The functional site could be either postsynaptic to the hair cell or postsynaptic to the lateral efferent input to spiral ganglion cell dendrites beneath IHCs. The presence of ␦1 postsynaptic to hair cells is consistent with the hypothesis that an excitatory amino acid is the neurotransmitter of hair cells (Annoni et al, 1984;Soto and Vega, 1988;Bledsoe et al, 1989; for review, see Eybalin, 1993;Puel, 1995). Spiral and vestibular ganglion neurons express many glutamate receptors including AMPA, kainate, and NMDA ionotropic receptors and several metabotropic receptors (Ryan et al, 1991;Eybalin, 1992b, 1995;Demêmes et al, 1995;Niedzielski and Wenthold, 1995;Usami and Ottersen, 1995).…”
Section: Discussionsupporting
confidence: 76%
“…Similar studies have suggested that the vestibular afferent neurotransmitter is an excitatory amino acid (Annoni et al, 1984;Soto and Vega, 1988;Bledsoe et al, 1989).…”
Section: Abstract: Cochlea; Vestibular End Organ; Hair Cells; Spiralsupporting
confidence: 58%
See 1 more Smart Citation
“…regions (Perkins & Stone, 1982;Cochran, 1983;Ganong et al 1983Ganong et al , 1986Ganong & Cotman, 1986), and interact with paired pulse potentiation of the perforant path in a manner consistent with a post-synaptic receptor blocker (Harris & Cotman, 1985). In addition, kynurenate blocks spontaneous synaptic events at the vestibular hair cell afferent, synapse of the frog (Annoni et al 1984). These observations are consistent with an action of these antagonists at a post-synaptic receptor type common to many excitatory amino acid synapses.…”
Section: Synaptic Antagonism By Kynurenate and Pbb-pzdasupporting
confidence: 80%
“…In addition, kynurenate and and pBB-PzDA are potent synaptic antagonists in several other C.N.s. excitatory pathways (Cochran, 1983;Ganong et al 1983;Annoni et al 1984;Davies et al 1984;Herrling, 1985).…”
Section: Synaptic Antagonism By Kynurenate and Pbb-pzdamentioning
confidence: 99%